Clinical and Radiological Outcomes of Minimally Invasive vs Conventional Surgery for Lumbar Spinal Stenosis: A Prospective Cohort Study - Samir Khan Kabir; Abdul Sattar; Muhammad Zahid Khan; Muhammad Arif Khan; Waqar Khan (Journal of Gandhara Medical and Dental Science, 2024)
Objective The objective of this study is to compare the clinical and radiological outcomes of minimally invasive surgery (MIS) versus conventional surgery for patients with lumbar spinal stenosis (LSS). Methods: This prospective cohort study was conducted at a tertiary care hospital in Peshawar, Pakistan, the study enrolled 200 patients diagnosed with symptomatic LSS, confirmed by MRI. Patients were assigned to MIS (n=100) or conventional surgery (n=100) groups based on surgeon discretion and patient preference. Preoperative and postoperative evaluations included clinical assessments using the Visual Analog Scale (VAS) for pain, Oswestry Disability Index (ODI), and patient satisfaction scores, alongside radiological assessments of spinal canal diameter and residual stenosis. Data analysis was performed using SPSS version 25.0, with a significance level set at p<0.05. Results: The MIS group exhibited significantly lower VAS scores (6 months: 2.8±1.2 vs. 4.5±1.5, p<0.01; 12 months: 2.5±1.1 vs. 4.2±1.3, p<0.01) and ODI scores (6 months: 18.4±5.2 vs. 25.6±6.3, p<0.01; 12 months: 17.8±4.9 vs. 24.8±6.0, p<0.01) compared to the conventional surgery group. Patient satisfaction was higher in the MIS group (85% vs. 70%, p<0.05). Radiological outcomes showed a greater increase in spinal canal diameter in the MIS group at 6 months (13.5±1.4 mm vs. 12.1±1.5 mm, p<0.01) and 12 months (13.2±1.3 mm vs. 11.8±1.4 mm, p<0.01) postoperatively. The incidence of residual stenosis was lower in the MIS group at both follow-ups (6 months: 10% vs. 25%, p<0.05; 12 months: 12% vs. 28%, p<0.05). Conclusion: MIS offers superior clinical and radiological outcomes compared to conventional surgery for LSS, with better pain relief, functional improvement, and patient satisfaction. The study supports MIS as a viable alternative to conventional surgery, though further research is needed to explore its long-term efficacy and safety. Keywords: lumbar spinal stenosis, minimally invasive surgery, conventional surgery, clinical outcomes, radiological outcomes, prospective cohort study.